POLITENESS STRATEGIES USED BY LIAM PAGE AND JOSIE IN FROVER MY GIRL MOVIE - Afiyah, Andi; Sunra, La (Journal of English Literature and Linguistic Studies, 2023)
This research analyzed “Forever My Girl” moviewith focuses onthe main character’s strategiesfor being politeness.This research focuses on charactersLiam Pageas male character and Josieas female characterin “Forever My Girl” movie.This researchaimed to identifypolitenessstrategiesandfactors influencedthem used certain strategiesin themovie “Forever My Girl”.The researcherutilized the Brown and Levinson approach (1987) to the data analysis.Theresearch applied the descriptive qualitative research design.The data analysis used interactivemodel analysiswhich includesdata reduction, data display and conclusion (Miles, Huberman &Saldana, 2014). The results of this research indicated that thecharacters in Forever My Girlmovie employed all the strategiesthose arebald-on record, positive politeness, negativepoliteness, and off-record.The factors which influenced the main characters in choosing certainstrategies were payoff and sociological variables. Furthermore,themale, andthefemalecharacter in “Forever My Girl” movie is more commonly employed positive politeness becausethey want to highlight the solidarity and intimacy toward the interlocutors.